Dispute Settlement in ASEAN: Legal Procedural Issue to Access - Somsack Hongvichit, (Technium Social Sciences Journal, 2025)
The Association of Southeast Asian Nations (ASEAN) establishes the ASEAN dispute settlement mechanism since 1996, but it has never been used by any ASEAN member states. In ASEAN, all ASEAN member states are required to settle all disputes amicably through diplomatic consultation and negotiation before referral to quasi-judicial under the ASEAN dispute settlement. This approach provides more flexibility and delay settling of dispute such as trade issue under the ASEAN Trade in Goods Agreement (ATIGA). In addition, certain trade issue under the ATIGA is not subject to be complained to the WTO dispute settlement. Therefore, some ASEN member states have to deal with their problems intra ASEAN under the ASEAN legal frameworks.